2017
DOI: 10.1111/inm.12418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating effectiveness in adolescent mental health inpatient units: A systematic review

Abstract: Adolescent mental health research is a developing area. Inpatient units are the most widely used acute element of adolescent mental health services internationally. Little is known about inpatient units, particularly when it comes to measuring improvement for adolescents. Clinical outcome measurement in the broad context has gathered momentum in recent years, driven by the need to assess services. The measurement of outcomes for adolescents who access inpatient care is critical, as they are particularly vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 38 publications
1
54
1
1
Order By: Relevance
“…Of the dearth of studies examining adolescent inpatient units, most have used quantitative methods of inquiry (Hayes et al, ; Indig et al, ; Lee, Martin, Hembry, & Lewis, ; Patterson et al, ; Rouski, Hodge, & Tatum, ; Seckman et al, ). Whilst this approach might be appropriate for some effectiveness and outcome studies, there are limitations when attempting to understand a specialized inpatient service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the dearth of studies examining adolescent inpatient units, most have used quantitative methods of inquiry (Hayes et al, ; Indig et al, ; Lee, Martin, Hembry, & Lewis, ; Patterson et al, ; Rouski, Hodge, & Tatum, ; Seckman et al, ). Whilst this approach might be appropriate for some effectiveness and outcome studies, there are limitations when attempting to understand a specialized inpatient service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, research is needed on how adolescents use the hospitalization event to build a positive perception of self, and how nurses use the relationship to help them begin this process. While this change in self or self‐perception is logically connected to a nursing relationship‐based focus (Geanellos, ), there is a paucity of youth inpatient outcomes studies and those that are published vary widely in quality and the measures used (Biering, ; Hayes, Simmons, Simons, & Hopwood, ). Moreover, the standardized survey‐type satisfaction instruments that are now available (Toomey et al., ) may not fit well with what children/adolescents and their families seek and how they frame improvement (Salamone‐Violi et al., 2015).…”
Section: Future Directionsmentioning
confidence: 99%
“…This was observed in a recent systematic review, which examined the effectiveness of adolescent inpatient units and adolescent outcomes (Hayes et al . ). The review found that several studies failed to report on important features of each inpatient unit, such as what nonpharmacological therapeutic interventions were delivered.…”
Section: Introductionmentioning
confidence: 97%
“…Inpatient units are known to be effective for the majority of adolescents in that they improve in at least one area of their symptomatology from admission to discharge (Bettmann & Jasperson 2009;Hayes et al 2018). Inpatient units play an important role in meeting the complex needs of adolescents within the continuum of care.…”
Section: Introductionmentioning
confidence: 99%